Implementasi Quizziz dan Youtube Dalam Meningkatkan Prestasi Akademik Akuntansi Keuangan dalam kegiatan PKL Siswa Kelas XI SMK Negeri 1 Jombang - Muaddab, Hafis - (Jurnal Pendidikan Akuntansi (JPAK), 2024)
The current problem at SMK Negeri 1 Jombang is that the learning outcomes for financial accounting practicum subjects during field Industrial practice (PKL) is not optimal. Therefore, this research investigates how to use Quizizz to improve learning outcomes and motivation of vocational school students during PKL. The results of the research obtained important data regarding the increase in student learning outcomes in field work programs in financial accounting subjects along with the use of a combination of direct learning with the Quizizz and YouTube applications. To facilitate communication, Whatsapp Group and Google Classroom media are used so that distance learning during the field work program for financial accounting subjects is easy for students to manage and understand. Quantitative research was conducted using descriptive data analysis based on Pre-Experimental Designs with One-Group Pretest-Posttest. The sample used in this research was 27 students from class XI AK 1, using a purposive sampling technique. Research data processing was carried out using the Wilcoxon hypothesis test and the N-Gain normality test. An important research finding found that the use of Quizizz media was quite effective in learning accounting material. The Wilcoxon test data concluded that the Ho result was declared correct and Ha was rejected, with a 2-tailed asymptotic significance value of 0.001 < 0.05 or autocorrelation occurred. The N-gain normality test found that the results of the N-gain normality test analysis data were at 58.4921%, thus it was concluded that it was quite effective.